2022
DOI: 10.1080/07853890.2022.2107233
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum hepatitis B virus DNA was a risk factor for hepatocellular carcinoma recurrence after liver transplantation

Abstract: Background Tumour characteristics and orthotopic liver transplantation (OLT) criteria are risks for recurrence of hepatocellular carcinoma (HCC). In Asia, most HCC is caused by chronic hepatitis B infection. Whether hepatitis B virus DNA (HBV DNA) is a risk factor for HCC recurrence after OLT is not clear. Patients and methods In this retrospective study, we classified patients into groups of detectable and undetectable HBV DNA, non-HCC recurrence, and recurrence and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has been established that certain tumor characteristics can lead to the recurrence of HCC, including the concentration of alpha fetoproteins, tumor diameter, macrovascular invasion, and extended orthotopic liver transplantation criteria ( 129 ). A recent study found that both pre-operative serum hepatitis B viral DNA and pre-operative prognostic nutritional index can potentially be used to predict HCC recurrence after liver transplantation ( 130 , 131 ). However, these studies all had small sample sizes or were conducted retrospectively and lack of molecular-biological investigations.…”
Section: Nets and Hepatocellular Carcinoma Recurrencementioning
confidence: 99%
“…It has been established that certain tumor characteristics can lead to the recurrence of HCC, including the concentration of alpha fetoproteins, tumor diameter, macrovascular invasion, and extended orthotopic liver transplantation criteria ( 129 ). A recent study found that both pre-operative serum hepatitis B viral DNA and pre-operative prognostic nutritional index can potentially be used to predict HCC recurrence after liver transplantation ( 130 , 131 ). However, these studies all had small sample sizes or were conducted retrospectively and lack of molecular-biological investigations.…”
Section: Nets and Hepatocellular Carcinoma Recurrencementioning
confidence: 99%